CODE-MIXING AND CODE SWITCHING TOWARD ENGLISH USE AT PONDOK PESANTREN NURUL JADID PAITON - PROBOLINGGO - DIAUL HAQ, DIQY (Language Horizon: Journal of Language Studies, 2013)
Studi tentangcode switchingdancode mixing adalah bagian darisosiolinguistik. Dua-dua nya memilikiarti yang sama. Code mixingadalah proses dimanapelakumemanjakandalam code-switching antarabahasasepertikecepatandan kepadatan, bahkan dalamkalimatdan frase yangtidak benar-benarmungkin untuk mengatakanpada waktu tertentubahasa yangmerekaberbicara. Penelitian ini membahascode switchingdan kode mixingantara orang Madura danbahasa Inggris yang digunakanoleh siswa dariLembaga Pengembangan Bahasa Asing (FLDI). Tujuandari penelitian ini adalahuntuk menggambarkanbagaimanacode switchingdankode mixing, yangterjadidiFLDI. Deskripsiini meliputi: (1) Apa jenisCode SwitchingdanCodeMixingyang dilakukan olehsiswaFLDIadalah, (2) Faktor-faktor apa saja yang membuatsiswa dalam menggunakan CodeSwitchingdanCode Mixing.Penelitian ini menggunakanmetode deskriptif kualitatifdan menggunakanteoriHymeyang disebutSPEAKING. Metodepengumpulan datayang digunakandalam penelitian ini adalahobservasi dan wawancara. Hasilnyamenunjukkan bahwa: (1) Code Switching(Situational CodeSwitching,Conversational CodeSwicthingdanMetaforaCodeSwitching)danCode Mixing(Penyisipan, Alternatif, dankongruen secara lexical) jenisdiproduksiolehstdentsdariFLDI, dan bahwa (2) Tempat,pelaku, tujuan, urutantindakan, dan kunciadalahfaktoryangmembuatsiswa melakukan codeswitchingdancode mixing. Keywords: code switching and code mixing, Bahasa Madura, Bahasa Inggris, Bahasa, Lembaga Pengembangan Bahasa Asing. Abstract The study of code switching and code mixing are parts of sociolinguistic. They have the same meaning. Code mixing is the process whereby speakers indulge in code-switching between languages of such rapidity and density, even within sentences and phrases that it is not really possible to say at any given time which language they are speaking. This study discusses code switching and code mixing between Madurese and English used by the students of Foreign Language Developmet Institute (FLDI). The purpose of this research is to describe how the code switching and code mixing, which happen in FLDI, is. The description includes: (1) What types of Code Switching and Code Mixing done by the students of FLDI are; (2) What factors make students do Code Switching and Code Mixing are. This study uses the descriptive qualitative method and uses the Hyme’s theory called SPEAKING. The data collection methods used in this study is observation and interview. The result shows that: (1) code switching (Situational Code Switching, Conversational Code Swicthing and Metaphorical Code Switching) and code mixing (Insertion, Alternation, and Congruent Lexicalization) types are produced by the stdents of FLDI ; and that (2)Setting, participant, ends, act sequence, and keys are the factors which make the students do the code switching and code mixing. Keywords: code switching and code mixing, Madurese, English, language, Foreign Language Development Institute.